2019
DOI: 10.3354/dao03394
|View full text |Cite
|
Sign up to set email alerts
|

Health assessment of the cleaner fish ballan wrasse Labrus bergylta from the British south-west coast

Abstract: Wild-caught ballan wrasse Labrus bergylta are translocated en masse from the British south-west coast to Scotland for use as cleaner fish to tackle Atlantic salmon Salmo salar sea lice infestations; however, very little is known about the background health status of this species. This is the first health assessment of wild ballan wrasse from the British south-west. Wildcaught ballan wrasse (n = 75) from coastal populations of Dorset and Cornwall were subjected to a full health screen for viral, bacterial and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…A pathogenic M. mobile was originally isolated from the gills of a freshwater fish, the tench Tinca tinca L, showing a characteristic fast gliding motion (Kirchhoff and Rosengarten, 1984). Other mycoplasmas have been reported historically from fish-derived cell lines (Emerson et al, 1979), and fish tissues, in particular, Acholeplasma laidlawii considered to be a non-pathogenic microorganism (McMurtrie et al, 2019). In the present study, all the samples with mycoplasma sequences showed co-infections with Endozoicomonadaceae.…”
Section: Discussionsupporting
confidence: 53%
“…A pathogenic M. mobile was originally isolated from the gills of a freshwater fish, the tench Tinca tinca L, showing a characteristic fast gliding motion (Kirchhoff and Rosengarten, 1984). Other mycoplasmas have been reported historically from fish-derived cell lines (Emerson et al, 1979), and fish tissues, in particular, Acholeplasma laidlawii considered to be a non-pathogenic microorganism (McMurtrie et al, 2019). In the present study, all the samples with mycoplasma sequences showed co-infections with Endozoicomonadaceae.…”
Section: Discussionsupporting
confidence: 53%
“…damselae has been reported from diseased rainbow trout during warm summer periods in Denmark (Pedersen et al, 1997), and Atlantic salmon have demonstrated susceptibility to disease under experimental conditions (Austin et al, 1997). Further work is needed however, to investigate its potential risks at cooler northern European climate conditions (McMurtrie et al, 2019).…”
Section: Bacteria and Fungimentioning
confidence: 99%
“…Systemic infection with Photobacterium damselae subsp. damselae (Pdd) (formerly Vibrio damselae ) was recently reported from a single wild‐caught ballan wrasse from the British south‐west coast during the warmest average water temperatures that year (McMurtrie et al, 2019). Photobacteriosis is a devastating fish disease in warm and temperate aquaculture locations, where a closely related subspecies, Photobacterium damselae subsp.…”
Section: Diseases Of Lumpfish and Wrassementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, concerns have been raised regarding bycatch of other valued species, such as brown crab Cancer pagurus , Atlantic Cod Gadus morhua , and European lobster Homarus gammarus (Grefsrud et al 2018:166–174). Since the wrasse fishery also has recently expanded in the southern regions of the UK and in Scotland (Riley et al 2017; McMurtrie et al 2019), there is an increasing need for better knowledge of how this fishery impacts target species and bycatch and a need to develop methods for accurate and efficient monitoring of the stocks.…”
Section: Species Depth Range (M) Life History Characteristics Norwegimentioning
confidence: 99%